Interleukin‐10 Gene Polymorphisms are Associated With Freedom From Treatment Failure for Patients With Hodgkin Lymphoma. (8th January 2013) - Schoof, Nils; Franklin, Jeremy; Fürst, Robert; Zander, Thomas; von Bonin, Frederike; Peyrade, Frederic; Trümper, Lorenz; Diehl, Volker; Engert, Andreas; Kube, Dieter; Re, Daniel
Abstract : CME Learning Objectives: Discuss whether and how genetic variations influence clinical outcomes of Hodgkin lymphoma patients. Evaluate evidence that proximal IL10 promoter gene variations are associated with clinical courses of Hodgkin lymphoma patients. Compare host genetic variations from different cytokine/cytokine receptor gene variations. Background: Hodgkin lymphoma (HL) is a lymphoid malignancy characterized by the production of various cytokines possibly involved in immune deregulation. Interleukin‐10 (IL‐10) serum levels have been associated with clinical outcome in patients with HL. Because host genetic variations are known to alter the expression and function of cytokines and their receptors, we investigated whether genetic variations influence clinical outcome of patients with HL. Methods: A total of 301 patients with HL who were treated within randomized trials by the German Hodgkin Study Group were included in this exploratory retrospective study. Gene variations of IL‐10 (IL‐10‐597AC, rs1800872; IL‐10‐824CT, rs1800871; IL‐10‐1087AG, rs1800896; IL‐10‐3538AT, rs1800890; IL‐10‐6208CG, rs10494879; IL‐10‐6752AT, rs6676671; IL‐10‐7400InDel ), IL‐13 (IL‐13‐1069CT, rs1800925; IL‐13Q144R, rs20541), and IL‐4R (IL‐4RI75V, rs1805010; IL‐4RQ576R, rs1801275) were genotyped. Results: Inferior freedom from treatment failure (FFTF) was found in patients harboring the IL‐10‐597AA, IL‐10‐824TT, or the IL‐10‐1087AA genotype. In contrast, the IL‐10‐1087G‐824C‐597C haplotype present in about 48% of analyzed HL patients is nominally significant for a better FFTF in a Cox‐Regression model accounting for stage and treatment. No associations were observed between the other IL‐10 gene variations, IL‐13‐1069CT, IL‐13Q144R, IL‐4RI75V, IL‐4RQ576R and the clinical outcome of patients with HL. Conclusions: Our study provides further evidence that proximal IL‐10 promoter gene variations are associated with clinical course of patients with HL. However, treatment success and survival rates are already at a very high rate, supporting the need to design studies focusing on identification of predictors to reduce the side effects of therapy. Abstract : Host genetic variations are known to alter the expression and function of cytokines and their receptors. This study investigated whether proximal IL‐10 promoter gene variations are associated with clinical course of patients with Hodgkin lymphoma. Abstract : 摘要 背景 . 霍奇金淋巴瘤（HL）是一种淋巴恶性肿瘤，其特征为可能参与免疫失调的多种细胞因子的产生。现已发现，白细胞介素‐10（IL‐10）血清水平与HL患者临床转归相关。由于宿主基因变异已知能够改变细胞因子及其受体的表达与功能，我们研究了基因变异是否影响HL患者的临床转归。 方法 . 本次探索性回顾性研究入组了德国霍奇金研究组开展的随机试验中接受治疗的301例HL患者。IL‐10基因变异（IL‐10‐597AC ，rs1800872；IL‐10‐824CT ，rs1800871；IL‐10‐1087AG ，rs1800896；IL‐10‐3538AT ，rs1800890；IL‐10‐6208CG ，rs10494879；IL‐10 ‐6752AT ，rs6676671；IL‐10‐7400InDel ）、IL‐13基因变异（IL‐13‐1069CT ，rs1800925；IL‐13Q144R ，rs20541）、IL‐4R基因变异（IL‐4RI75V ，rs1805010；IL‐4RQ576R ，rs1801275）进行了基因分型。 结果 . 伴有IL‐10‐597AA 、IL‐10‐824TT 或IL‐10‐1087AA 基因型的患者中避免治疗失败（FFTF）的结果较差。相反，关于分期和治疗的Cox回归模型显示，所分析的HL患者中有48%伴有IL‐10 ‐1087G ‐824C ‐597C 单体型者FFTF结果较好。其他IL‐10基因变异、IL‐13 ‐1069CT 、IL‐13Q144R 、IL‐4RI75V 、IL‐4RQ576R 与HL患者临床转归之间未见相关性。 结论 . 我们的研究提供了进一步证据，表明近端IL‐10启动子基因变异与HL患者临床过程相关。然而，治疗成功率和生存率都已达到很高的水平，说明有必要设计研究来识别能够减少治疗副反应的预测因子。